(untitled) (Dhaka University Journal of Biological Sciences, 2020)
A pot experiment was conducted to evaluate the effects of zinc and vermicompost on the growth, yield and nutrient content of soybean (Glycine max L.) plant. The treatment variables were control (‒Zn and ‒VC), VC 5 ton/ha, Zn 1 kg/ha, Zn 2 kg/ha, Zn 3 kg/ha, Zn 1 kg/ha + VC 5 ton/ha, Zn 2 kg/ha + VC 5 ton/ha and Zn 3 kg/ha + VC 5 ton/ha. Application of zinc and vermicompost showed a significant effect on the growth parameters and macro- and micronutrients uptake by the plant. The highest average plant height (164 cm), leaf number (80 nos./plant), leaf area (3360 cm2/plant), fresh weight (49.03 gm/plant), dry weight (24.54 gm/plant), fruit length (9.4 cm), fruit number per plant (5 nos. /plant) were recorded for Zn 1 kg/ha + VC 5 ton/ha treatment while the lowest values were observed in control at harvest. Results of the growth parameters varied significantly (p ≤ 0.05) with time. It was observed that, the overall best growth performance was achieved in Zn 1 kg/ha + VC 5 ton/ha. Dhaka Univ. J. Biol. Sci. 29(2): 201-208, 2020 (July)